Electrophotographic member, and electrophotographic image forming apparatus
By using dispersants of specific structures, the environmental unfriendliness and degradation of the surface layer material of the intermediate transfer belt is solved, and high-quality and long-term stable development effects are achieved.
Patent Information
- Application Number
- JP2023121642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, the surface layer materials used in the intermediate transfer belt have environmental unfriendliness problems and are difficult to maintain high-quality development performance for a long time, especially because the fluoroalkyl chains of long carbon chains are difficult to decompose, resulting in environmental pollution and development performance degradation.
Compounds with specific structures are used as dispersants, including compounds with fluoroalkyl chains bonded to fluorine atoms, and combined with dispersants with heterocyclic monoterpene structures, forming surface layer materials with high dispersion and environmental protection, ensuring the uniform distribution and stability of PFPE on the surface layer.
It realizes environmentally friendly high-quality development performance, can stably form high-quality electrophotographic images over a long period of time, and improves the development performance and durability of the intermediate transfer belt.
Smart Images

Figure 2025018160000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrophotographic member used as an intermediate transfer member in an electrophotographic image forming apparatus such as a copying machine or a printer, and to an electrophotographic image forming apparatus equipped with the electrophotographic member. [Background technology]
[0002] In electrophotographic image forming devices, the tandem method is widely used in which toner images of yellow (Y), magenta (M), cyan (C), and black (K) are superimposed on an intermediate transfer belt as an intermediate transfer member, and then all of the toner images are transferred onto paper at once to obtain a full-color image.
[0003] The intermediate transfer belt used here is generally a semiconductive belt, and a typical example is a belt formed by dispersing carbon black in a resin such as polyimide or polyamideimide. In such an electrophotographic device that requires high speed and high durability, further improvement in the transfer characteristics of the intermediate transfer belt is required. As one of such improvements, it has been proposed to reduce the adhesion of toner to the surface of the surface layer by incorporating oil-like perfluoropolyether (hereinafter also referred to as "PFPE"), which has a very small surface free energy, into the surface layer of the intermediate transfer belt.
[0004] Paragraph 0071 of Patent Document 1 discloses that a compound having a perfluoroalkyl chain and a moiety having affinity for hydrocarbons is used as a dispersant to disperse PFPE well in the matrix resin in the surface layer. The longer the carbon number of the perfluoroalkyl group, the higher the affinity for PFPE. Therefore, from the viewpoint of dispersibility of PFPE, a compound having a perfluoroalkyl chain with a long carbon number is advantageous. However, compounds having a long carbon number perfluoroalkyl chain are difficult to decompose and tend to remain in the environment. In recent years, restrictions on the use of compounds having six consecutive carbons bonded to fluorine atoms, such as perfluorohexanoic acid (PFHxA), have been considered. For this reason, it has been proposed to use a compound having a structure in which the number of consecutive carbon atoms bonded to fluorine atoms is four or less as a dispersant for PFPE, as a compound with a relatively high decomposability of the perfluoroalkyl chain portion. Patent Document 2 discloses the use of an acrylic resin having a side chain with an ether structure introduced therein so that the number of consecutive carbons bonded to fluorine atoms is three or less as a dispersant for PFPE. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-231964 A [Patent Document 2] JP 2022-167788 A Summary of the Invention [Problem to be solved by the invention]
[0006] According to the study by the present inventors, the fluorine-containing copolymer according to Patent Document 2 has high adsorption to PFPE by having many fluorine atoms in the side chain portion while limiting the number of consecutive carbon atoms to which fluorine atoms are bonded to 3 or less. However, the copolymer having such a structure has a complicated structure in which the perfluoroalkyl chain is divided by an ether structure, and therefore is expensive.
[0007] At least one aspect of the present disclosure is directed to an electrophotographic member that is environmentally friendly and contributes to the formation of high-quality electrophotographic images over a long period of time. It is directed to an image forming device. [Means for solving the problem]
[0008] In accordance with at least one aspect of the present disclosure, there is provided an electrophotographic member having at least a base layer and a surface layer, An electrophotographic member is provided, wherein the surface layer contains the following A, B, and C: A: Compound 1 having a structure represented by the following formula (I) and a structure represented by the following formula (II) B: Perfluoropolyether C: Binder resin [ka] In formula (I), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rf 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms, and in formula (II), R 21 represents a hydrogen atom or a methyl group, R 22 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rt 1 represents a structure having a polycyclic monoterpene.
[0009] Furthermore, according to at least one embodiment of the present disclosure, there is provided an electrophotographic image forming apparatus comprising an image carrier that carries a toner image, and an intermediate transfer member that secondarily transfers the toner image primarily transferred from the image carrier to a recording material, the intermediate transfer member being the electrophotographic member described above. Effect of the Invention
[0010] According to at least one aspect of the present disclosure, it is possible to provide an electrophotographic member that is environmentally friendly and contributes to the formation of high-quality electrophotographic images over a long period of time. Also, according to at least one aspect of the present disclosure, it is possible to provide an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images. [Brief description of the drawings]
[0011] [Figure 1]FIG. 1 is a cross-sectional view showing an example of an image forming apparatus using an electrophotographic belt. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an electrophotographic belt. [Diagram 3] FIG. 1 is an illustration of the probable mechanism of dispersion of PFPE by compounds according to the present disclosure. [Figure 4] FIG. 2 is an explanatory diagram of the dispersion state of PFPE using a dispersant not having the structure of formula (II). [Diagram 5] FIG. 2 is a schematic diagram of an electrophotographic member according to a second embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. In addition, when a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ. Furthermore, in the present disclosure, "Ω / □" is a unit of surface resistivity and means "Ω / square".
[0013] The present inventors have conducted extensive research to obtain a compound that is exempt from the regulations on perfluorohexanoic acid (PFHxA), has four or less consecutive carbon atoms to which fluorine atoms are bonded, and has a simpler structure than the compound proposed in Patent Document 2, while allowing PFPE to be well dispersed in a (meth)acrylic resin. As a result, the inventors have found that compounds having a structure represented by the following formula (I) and a structure represented by the following formula (II) are effective in achieving the above object. [ka]
[0014] In formula (I), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rf 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms. 21 represents a hydrogen atom or a methyl group, R 22 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rt 1 represents a structure having a polycyclic monoterpene.
[0015] The compounds having the structure represented by the above formula (I) and the structure represented by the above formula (II) are not subject to the regulation related to PFHxA because the number of consecutive carbons to which fluorine atoms are bonded is 4 or less, and are excellent in environmental consideration. Here, since Rf1 is a perfluoroalkyl group having 1 to 4 carbon atoms, the adsorptivity to PFPE is lower than that of the dispersant related to Patent Document 2. However, as shown in FIG. 3, the molecular chain 30 of compound 1 It is considered that compound 1 is adsorbed at a certain distance from PFPE due to steric hindrance caused by bulky structure of Rt1 in the structure of formula (II) in 1. As a result, the proximity of PFPE domain 303 and PFPE domain 305 is also hindered. As a result, the dispersibility of PFPE in the surface layer is improved. For this reason, it is considered that the compound according to the present disclosure can disperse PFPE well in the binder resin.
[0016] On the other hand, in the case of a dispersant not having the structure of formula (II), the steric hindrance by Rt1 does not act, so that, as shown in Fig. 4, the molecular chain 401 of the dispersant is non-uniformly adsorbed to the PFPE, and it may not be possible to prevent the PFPE domain 403 from approaching the PFPE domain 405. As a result, it is considered that the PFPE domains are united to form a large domain.
[0017] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. However, the dimensions, materials, shapes, and relative positions of the components described in the following embodiments may be changed as appropriate depending on the configuration of the device to which the present invention is applied and various conditions, and are not intended to limit the scope of the present invention to these alone.
[0018] [Electrophotographic materials] The electrophotographic member has at least a base layer and a surface layer. One embodiment of the electrophotographic member 7 according to the present disclosure is, for example, an endless electrophotographic belt having a two-layer structure of a base layer 31 and a surface layer 32 provided on the outer peripheral surface of the base layer 31, as shown in Fig. 2. The surface layer 32 contains a binder resin 33 and a domain 34 containing PFPE.
[0019] The configuration of the electrophotographic member is not limited to the above-mentioned two-layer laminate. For example, a primer layer (not shown) for improving adhesion between the base layer 31 and the surface layer 32, a stress relaxation layer for suppressing cracking of the surface layer 32, and an intermediate layer for suppressing bleeding (none of which are shown) may be provided.
[0020] <base layer> The material constituting the base layer 31 is preferably a resin having mechanical strength and flex resistance required for an intermediate transfer belt for an electrophotographic device. Specific examples include the following: polyamide, polyacetal, polyarylate, polycarbonate, polyphenylene ether, polyethylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polysulfone, polyether sulfone, polyphenyl sulfide, polybutylene terephthalate, polyether ether ketone, polyvinylidene fluoride, polyvinyl fluoride, polyether amide copolymer, polyurethane copolymer, polyimide, polyamide imide, etc. It is formed from one of these resins or a mixture of these, and typically has a conductive material added thereto to impart electrical conductivity. The base layer preferably comprises a polyimide, which gives the base layer excellent strength.
[0021] The conductive material may be inorganic carbon-based conductive particles such as carbon black, carbon fiber, or carbon nanotubes, or metal oxide particles such as zinc antimonate particles, zinc oxide particles, tin oxide particles, or titanium oxide particles. By mixing such conductive materials, the volume resistivity can be increased to 1×10 8 ~1×10 12 It is preferable that the surface resistivity is adjusted to within the range of 1×10 8 ~1×10 14 It is preferable that the resistance be adjusted to within the range of [Ω / □].
[0022] Volume resistivity is 10 12 When the volume resistivity is less than 10 [Ω·cm], the primary transferability or secondary transferability by applying a predetermined transfer bias is good. 8 [Ω cm] or more In this case, the resistance unevenness is small, and image defects such as transfer unevenness are unlikely to occur. In addition, by setting the surface resistivity of the base layer within the above range, it is possible to reduce image defects caused by separation discharge when the recording material is separated from the intermediate transfer belt and toner scattering. The thickness of the base layer 31 is preferably 40 μm to 200 μm in order to obtain excellent mechanical strength and bending resistance.
[0023] It is also preferable that the electrical resistance of the electrophotographic member for electrophotography after the surface layer is formed on the base layer shows a similar value. For this reason, it is preferable that the surface layer of the electrophotographic member is also semiconductive. That is, the volume resistivity of the surface layer of the electrophotographic member is 10 8 ~10 12 It is preferable that the surface resistivity is adjusted to the range of 10 8 ~10 14 It is preferable that the surface layer is adjusted to the range of [Ω / □]. In order to adjust the volume resistivity and surface resistivity of the electrophotographic member, the surface layer may contain a conductive agent. The conductive agent contained in the surface layer may be the same as the conductive agent (conductive substance) that can be used in the base layer.
[0024] <Surface layer> The surface layer 32 is formed on the outer peripheral surface side of the base layer 31, and serves as the outermost layer of the electrophotographic member. The surface layer contains the following A, B, and C. A: Compound 1 having a structure represented by formula (I) and a structure represented by formula (II) B: Perfluoropolyether C: Binder resin
[0025] In addition to the above A, B, and C, the surface layer 32 may contain other materials such as a photopolymerization initiator and a conductive substance, as long as the effects of the present disclosure are not impaired. Whether a domain contains PFPE (preferably as a major component) can be confirmed by observing fragments of fluorocarbon ether structures derived from PFPE from the domain using energy dispersive X-ray analysis (EDX) or TOF-SIMS.
[0026] Preferably, the PFPE-containing domain and the binder resin are phase-separated in the surface layer 32. For example, the surface layer is phase-separated into the PFPE-containing domain and the binder resin-containing matrix.
[0027] In the surface layer of the electrophotographic member according to the first embodiment of the present disclosure, the domains containing PFPE can be finely dispersed in the matrix containing the binder resin in the thickness direction of the surface layer by using the compound 1 according to A above. This allows PFPE to be continuously present on the surface of the electrophotographic member. That is, an intermediate transfer belt having PFPE on the outer surface, which is the toner image bearing surface, shows excellent secondary transferability, but the PFPE on the outer surface disappears when used for forming electrophotographic images over a long period of time. Therefore, in order to continuously maintain high secondary transferability, it is preferable to supply PFPE from the inside. For this purpose, it is effective to make PFPE exist in the form of domains in the thickness direction of the surface layer. And, by using the compound 1 according to A above according to the present disclosure, fine domains of PFPE can be present in the thickness direction of the surface layer.
[0028] By using the compound 1 according to the present disclosure, aggregation of PFPEs in the coating material for forming a surface layer can be effectively suppressed. As a result, when the cross section of the surface layer is observed using a scanning electron microscope, the average major axis of the domains containing PFPE can be made to exist in the surface layer with a small size such as 1 to 70 nm, particularly 25 to 70 nm. By allowing domains containing PFPE of such a size to exist in the surface layer, the glossiness of the surface of the surface layer, for example, the glossiness measured at an incident angle of 20°, can be increased to 70 to 90 GU (Glos s Unit), particularly, a high gloss such as 75 to 85 GU. Increasing the gloss of the surface of the electrophotographic member is advantageous in detecting a toner image (patch image) with high accuracy for controlling image forming conditions, for example, when the electrophotographic member is used as an intermediate transfer member.
[0029] Although the domain is preferably substantially composed of PFPE, in addition to PFPE, chemical species other than PFPE may be present in the domain, and additives compatible with PFPE may be added for the purpose of adjusting other properties, within the scope of the effect of the present disclosure. Furthermore, even if the domain is not completely filled with PFPE and voids exist, the effect of the present disclosure can be exhibited.
[0030] Generally, even when phase separation occurs, the composition of each component is not strict. Even when phase separation occurs with a clear interface, each phase may contain a small amount of the component of the other phase. Also, academically, it is said that an intermediate composition exists at the interface with a very narrow width of about 10 nm.
[0031] In the electrophotographic member according to the second embodiment of the present disclosure, as shown in Fig. 5, in surface layer 32, some of domains 501 containing PFPE are connected to each other (interconnected), and flow paths of PFPE indicated by arrows 505 are formed in matrix 503 containing a binder resin. In a surface layer having such a configuration, PFPE in the surface layer can be more stably transferred to surface 507 of the surface layer. Therefore, when the electrophotographic member is used as an intermediate transfer belt, even when a large number of electrophotographic images are formed, the PFPE on the surface of the surface layer is unlikely to be depleted. The fact that the domains have an interconnected structure can be confirmed by cutting out a sample from the surface layer, exposing a cross section of the surface layer in the full thickness direction, removing the PFPE, and then observing the surface of the sample corresponding to the cross section in the thickness direction of the surface layer and the surface corresponding to the outer surface of the surface layer with a scanning electron microscope (SEM). The method of removing the PFPE will be described later.
[0032] The interconnect structure will now be described. As in the surface layer according to the first embodiment, by having a large number of domains containing PFPE in the thickness direction of the surface layer, the PFPE can be gradually exuded to the surface of the surface layer, and the high toner releasability of the surface of the surface layer can be continuously maintained. However, when each domain exists independently, the migration speed of the PFPE to the surface may be slow. That is, when the PFPE on the surface of the surface layer disappears after forming a large number of electrophotographic images, it is assumed that it takes time to recover the high toner releasability of the surface of the surface layer. Therefore, by connecting the domains containing PFPE to each other in the surface layer, the PFPE present inside the surface layer can be more efficiently migrated to the outer surface of the surface layer. As a result, the high secondary transferability can be more stably maintained.
[0033] Although the domain is preferably substantially composed of PFPE, in addition to PFPE, chemical species other than PFPE may be present in the domain, and additives compatible with PFPE may be added for the purpose of adjusting other properties, within the scope of the effect of the present disclosure. Furthermore, even if the domain is not completely filled with PFPE and voids exist, the effect of the present disclosure can be exhibited.
[0034] A preferred embodiment of the interconnection structure will now be described. In an electrophotographic member, perfluoropolyether is removed from a surface layer to produce a surface layer from which perfluoropolyether has been removed. The surface layer from which perfluoropolyether has been removed preferably has voids having openings on its outer surface. Then, the total volume of the voids from which perfluoropolyether has been removed is determined to be 1 / 100 of the total volume of the voids. The ratio of the void volume to the volume of the surface layer when it is assumed to be solid is preferably 8.0 to 25.0%, more preferably 10.0 to 20.0%, and even more preferably 13.0 to 20.0%.
[0035] When the void volume ratio is within the above range, the domains are easily connected to each other, and the PFPE is easily supplied to the outermost surface for a longer period of time. The void volume ratio can be increased by the domains containing PFPE being connected to each other in the process of forming the surface layer. Therefore, in order to increase the void volume ratio, it is effective to use a low-viscosity PFPE as the PFPE used in forming the surface layer, and / or to increase the temperature of the coating film of the coating material for forming the surface layer during curing by UV irradiation in the process of forming the surface layer, thereby increasing the fluidity of the PFPE.
[0036] In addition, even when the surface layer is provided with a structure in which domains containing PFPE are linked to each other, compound 1 according to the present disclosure plays an important role. That is, as described above, the interconnected structure of domains containing PFPE is formed by mutually linking PFPE-containing domains that are isolated from each other in the coating film of the coating material for forming the surface layer during the curing process of the coating film. At this time, if the size of the isolated PFPE-containing domain before linking to each other is large, the size of the PFPE domain after linking to each other also becomes large. As a result, the gloss of the surface layer may increase. In addition, PFPE may migrate excessively to the surface of the surface layer, leading to early depletion of PFPE. Therefore, it is preferable to reduce the size of the isolated PFPE-containing domain in the coating film of the coating material for forming the surface layer formed in the process of forming the surface layer. For this purpose, it is effective to use compound 1 according to the present disclosure.
[0037] The unit area (1 μm 2 The ratio of the total area of the openings per unit area (opening area ratio) is preferably 10.0 to 35.0%, more preferably 17.0 to 30.0%, and even more preferably 19.0 to 25.0%.
[0038] When the opening area ratio is within the above range, the speed at which the PFPE migrates to the outer surface of the surface layer can be more favorable. When the opening area ratio is 10.0% or more, the amount of PFPE exposed per unit time is appropriate, and the releasability is more likely to be improved. When the opening area ratio is 35.0% or less, the PFPE is less likely to be depleted, and the releasability is more likely to be maintained for a longer period of time. The open area ratio can be increased by decreasing the viscosity of the PFPE and increasing the temperature during UV treatment. Conversely, the open area ratio can be decreased by increasing the viscosity of the PFPE and decreasing the temperature during UV treatment.
[0039] In addition, the unit area (1 μm 2The number of openings per 1 μm is preferably 10 to 500, more preferably 135 to 300, and even more preferably 140 to 250. 2 ) is within the above range, the PFPE is likely to migrate uniformly to the outer surface of the surface layer. Number of openings (pieces / 1μm 2 Since the number of openings increases by improving the dispersibility of the PFPE domains (reducing the particle size), the number of openings can be increased by increasing the amount of dispersant added. Conversely, the number of openings can be reduced by reducing the amount of dispersant added and decreasing the dispersibility of the PFPE domains.
[0040] <Binding resin> The surface layer contains a binder resin. The binder resin may be any known binder resin for electrophotographic members such as intermediate transfer belts. The binder resin preferably contains at least one resin selected from the group consisting of (meth)acrylic resins and epoxy resins. The binder resin more preferably contains (meth)acrylic resin. The (meth)acrylic resin is preferable from the viewpoints of dispersing the PFPE, ensuring adhesion to the base layer 31, and ensuring mechanical strength properties. As the (meth)acrylic resin, a methacrylic resin or an acrylic resin is preferably used. Hereinafter, the methacrylic resin and the acrylic resin are collectively referred to as a (meth)acrylic resin.
[0041] Examples of the polymerizable monomer for forming the (meth)acrylic resin include at least one selected from the group consisting of the following (i) and (ii). At least one selected from the group consisting of the following (i) is preferable. As the polymerizable monomer, it is also possible to use those commercially available as paints.
[0042] (i) at least one acrylate selected from the group consisting of pentaerythritol triacrylate, pentaerythritol tetraacrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexaacrylate, alkyl acrylate, benzyl acrylate, phenyl acrylate, ethylene glycol diacrylate, and bisphenol A diacrylate;
[0043] (ii) at least one methacrylate selected from the group consisting of pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, ditrimethylolpropane tetramethacrylate, dipentaerythritol hexamethacrylate, alkyl methacrylate, benzyl methacrylate, phenyl methacrylate, ethylene glycol dimethacrylate, and bisphenol A dimethacrylate;
[0044] Among these, high hardness is preferable in consideration of rubbing against other members such as a photoreceptor and a cleaning blade. For this reason, it is preferable to use a large amount of bifunctional or higher crosslinkable monomers in the (meth)acrylic resin to increase the hardness. In addition, in order to form the (meth)acrylic resin from such polymerizable monomers, there is a method of adding a photopolymerization initiator and polymerizing with an electron beam or ultraviolet light.
[0045] Examples of the photopolymerization initiator include radical-generating photopolymerization initiators such as benzophenone, thioxanthone, benzyl dimethyl ketal, α-hydroxyketone, α-hydroxyalkylphenone, α-aminoketone, α-aminoalkylphenone, monoacylphosphine oxide, bisacylphosphine oxide, hydroxybenzophenone, aminobenzophenone, titanocene, oxime ester, and oxyphenylacetic acid ester. The content of the binder resin in the surface layer is preferably from 20 to 90% by mass, and more preferably from 40 to 70% by mass, based on the mass of the surface layer.
[0046] <Perfluoropolyether> Perfluoropolyether (PFPE) is an oligomer or polymer having perfluoroalkylene ether as a repeating unit. PFPE is not particularly limited, and known ones can be adopted. Preferable is PFPE having a structure represented by the following formula (III) in the molecule. [ka]
[0047] In formula (III), a, b, c, d, e, and f each independently represent 0 or a positive integer, satisfying 1≦a+b+c+d+e+f≦600, and at least one of a, b, c, and d is a positive integer. In addition, in formula (III), each repeating unit may be present in a plurality of positions in the PFPE, that is, the PFPE represented by formula (1) may be a block copolymer or a random copolymer.
[0048] The perfluoropolyether preferably has at least one structure selected from the group consisting of the following formulas (IV) to (VII) in the molecule. [ka]
[0049] In formula (IV), n is a positive number. [ka]
[0050] In formula (V), n' is a positive number. [ka]
[0051] In formula (VI), n' is a positive number. [ka]
[0052] In formula (VII), n′″ and m′ are each independently a positive number.
[0053] The viscosity of the PFPE at a temperature of 20° C. is preferably 100 mPa·s to 2500 mPa·s, more preferably 100 mPa·s to 1000 mPa·s. PFPE in such a viscosity range contributes to stable migration to the surface of the surface layer. The viscosity of the PFPE can be measured, for example, using a Brookfield type rotational viscometer type B in accordance with Japanese Industrial Standards (JIS) K7117-1:1999.
[0054] Examples of commercially available PFPEs having the above viscosity range include "Fluorolink MD700" (viscosity 850 mPa / s) and "Fomblin D2" (viscosity 150 mPa·s). Note that all of these PFPEs have the structure of the above formula (VI) in their molecules.
[0055] Here, when the surface layer is the surface layer according to the first embodiment, it is preferable to use a PFPE having a high viscosity within the above-mentioned viscosity range, specifically, for example, 350 to 2000 mPa·s, particularly 500 to 1000 mPa·s. By using a PFPE within this range, the domains containing PFPE can be finely dispersed in the surface layer in a state where they are independent of each other. Therefore, it is easy to supply PFPE to the surface for a long time, and it is easy to maintain releasability for a long time. In addition, even if the domains containing PFPE exist independently of each other, they can stably migrate to the surface of the surface layer.
[0056] On the other hand, when the surface layer is the surface layer according to the second embodiment, it is preferable to use a PFPE having a low viscosity within the above range, specifically, for example, 30 to 550 mPa·s, particularly 50 to 200 mPa·s, and further 50 to 150 mPa·s. By using a PFPE within this range, a surface layer having a connection structure between domains containing PFPE can be more easily formed. That is, as described above, the viscosity of the PFPE in the domains can be reduced when the coating film of the coating material for forming the surface layer is heated. As a result, the domains can be more easily connected to each other in the process of proceeding with the curing of the coating film. In addition, by containing a PFPE having the above viscosity range in the domains connected to each other, the PFPE can be stably transferred to the surface of the surface layer.
[0057] The weight average molecular weight Mw of PFPE is preferably 100 or more and 20000 or less from the viewpoint of migration of PFPE to the surface of an electrophotographic member. The weight average molecular weight here is a value obtained by dissolving PFPE in Zeorora H (manufactured by Zeon Corporation) and measuring the liquid with a liquid chromatography analyzer (manufactured by Shimadzu Corporation). The compound name of Zeorora H is 1,1,2,2,3,3,4-heptafluorocyclopentane.
[0058] The content of PFPE in the surface layer is preferably 20 to 40 mass %, more preferably 25 to 35 mass %, based on the mass of the surface layer (including the mass of PFPE). When the content is 20 mass % or more, the low adhesion of the surface layer is more easily maintained. When the content is 40 mass % or less, the film strength is easily increased. By adjusting the PFPE content within the above range, even when repeated transfers are performed, PFPE can be supplied to the surface of the intermediate transfer belt from within the surface layer of the intermediate transfer belt, making it easier to suppress a decrease in the releasability of the intermediate transfer belt surface.
[0059] <Dispersant> The surface layer contains compound 1 having the structure represented by the following formula (I) and the structure represented by the formula (II) as a dispersant for dispersing perfluoropolyether. The structure represented by formula (I) has a small number of carbon atoms bonded to fluorine and is an environmentally friendly structure. In addition, as described above, it is considered that compound 1 has a structure represented by formula (II), which suppresses the adsorption or proximity of dispersants to each other, and is adsorbed to perfluoropolyether at a certain distance, and is evenly arranged on the surface of perfluoropolyether. This is considered to be due to the fact that the structure represented by formula (II) has a three-dimensional steric structure, which prevents dispersants from being entangled with each other and makes it easy for them to have a repulsive force structurally. [ka]
[0060] In formula (I), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rf 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms. 21 represents a hydrogen atom or a methyl group, R 22 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rt 1 represents a structure having a polycyclic monoterpene. The structure represented by formula (I) can be obtained by using, for example, 1H,1H,2H,2H-nonafluorohexyl (meth)acrylate, 2,2,3,3,4,4,4-heptafluorobutyl (meth)acrylate, or the like as a monomer.
[0061] R in formula (I) 12 Rf represents a single bond or an alkylene group having 1 to 3 carbon atoms, and is preferably an alkylene group having 1 or 2 carbon atoms. 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms (preferably 2 to 4 carbon atoms, more preferably 3 or 4 carbon atoms).
[0062] Rf 1Examples of the structures include the following structures (Rf1-1) to (Rf1-8). (Rf1-3) and (Rf1-5) are preferred. [ka]
[0063] R in the formula (II) 22 Rt represents a single bond or an alkylene group having 1 to 3 carbon atoms, and preferably represents a single bond or an alkylene group having 1 carbon atom. 1 Rt represents a structure having a polycyclic monoterpene. 1 Examples of the structure having a polycyclic monoterpene include the structures (Rt1-1) to (Rt1-8) shown below. (Rt1-1) and (Rt1-8) are preferred. As the structure having a polycyclic monoterpene, (Rt1-1) is more preferred.
[0064] The structure of formula (II) can be formed, for example, by using (meth)acrylic monomers having the structures (Rt1-1) to (Rt1-8). Specific examples include isobornyl (meth)acrylate and adamantan-1-yl (meth)acrylate. [ka]
[0065] The content of the structure represented by formula (I) in compound 1 is preferably 10 to 75 mass%, more preferably 12 to 65 mass%. The content of the structure represented by formula (II) in compound 1 is preferably 25 to 90 mass%, more preferably 35 to 88 mass%. When it is in the above range, the above-mentioned dispersion effect due to the structure represented by formula (II) is easily obtained.
[0066] Compound 1 is a copolymer having a structure represented by formula (I) and a structure represented by formula (II). Compound 1 is, for example, a (meth)acrylic resin. Compound 1 may also have a structure corresponding to at least one other (meth)acrylate selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate, to the extent that the effect of the present disclosure is not impaired. That is, compound 1 may be a copolymer of three or more types of monomers including other (meth)acrylates.
[0067] For example, compound 1 may further have a structure represented by formula (III). For example, compound 1 may contain the structure represented by formula (III) in an amount of preferably 0 to 30% by mass, more preferably 0 to 25% by mass. [ka] In formula (III), R 31 represents a hydrogen atom or a methyl group, R 32 represents an alkyl group having 1 to 4 carbon atoms (preferably 1 or 2, more preferably 1).
[0068] Moreover, from the viewpoint of the dispersion effect in perfluoropolyether and the connectivity of domains, the weight average molecular weight of compound 1 is preferably 15,000 to 80,000, and more preferably 20,000 to 40,000.
[0069] When the weight average molecular weight is 15,000 or more, the steric hindrance effect is improved, and the effect of suppressing aggregation between perfluoropolyethers is more easily obtained. Therefore, the domain size is likely to be small. Also, when the molecular weight is 80,000 or less, it is easily dissolved in a solvent, etc.
[0070] The weight average molecular weight is measured by gel permeation chromatography (GPC), the measurement method of which will be described later. The content of Compound 1 is preferably from 5% by mass to 30% by mass, and more preferably from 15% by mass to 25% by mass, based on the mass of the total solid content in the surface layer.
[0071] <Conductive agent> In order to impart electrical conductivity to the surface layer, the surface layer may contain a conductive agent, such as inorganic carbon-based conductive particles, such as carbon black, carbon fiber, and carbon nanotubes, and metal oxides, such as zinc antimonate, zinc oxide, tin oxide, and titanium oxide.
[0072] The thickness of the surface layer is preferably 2 to 20 μm, and more preferably 3 to 10 μm. When the thickness of the surface layer is 2 μm or more, durability is likely to be improved. On the other hand, when the thickness is 20 μm or less, folding endurance is likely to be good.
[0073] <Method of Manufacturing Electrophotographic Member> A specific method for producing the electrophotographic member will be described below, but the method for producing the electrophotographic member is not limited to the following method. The base layer of the electrophotographic member can be prepared by the following method. For example, in the case of a thermosetting resin such as polyimide, a conductive agent, carbon black, is dispersed in a varnish together with a precursor of the thermosetting resin or a soluble thermosetting resin and a solvent, and the varnish is coated on the mold of a centrifugal molding machine.The coated film is then baked to form a semiconductive film.
[0074] When a thermoplastic resin is used, the conductive carbon black is mixed with the thermoplastic resin, and if necessary, additives are added, and the mixture is melt-kneaded in a twin-screw kneader or the like to produce a semiconductive resin composition. Next, the resin composition is melt-extruded into a sheet, film, or seamless belt to obtain a semiconductive film. Seamless belts can be produced by either a method of extruding a belt from a cylindrical die or a method of extruding a sheet molded by extrusion. Alternatively, the laminate may be seamlessly formed by joining the laminated sheets together. In addition to this molding method, the laminated laminate may be formed by using a heat press or an injection molding. The thickness of the semiconductive film serving as the base layer is preferably 30 μm or more and 150 μm or less.
[0075] In addition, in order to strengthen the mechanical strength and durability of the electrophotographic member, it is preferable to carry out a crystallization treatment. For example, the crystallization treatment is carried out by annealing at a temperature equal to or higher than the glass transition temperature of the resin used, which can promote the crystallization of the resin used. The electrophotographic member thus obtained is not only excellent in mechanical strength and durability, but also excellent in abrasion resistance, chemical resistance, sliding properties, toughness and flame retardancy.
[0076] <Method of forming surface layer> The method for forming the surface layer in which independent domains containing PFPE are dispersed in the thickness direction according to the first embodiment can be exemplified by the following method. First, the binder resin or binder resin raw material (monomer, oligomer, etc.), PFPE, and compound 1, which are the above-described constituent members of the surface layer, are dissolved, dispersed, or dissolved and dispersed in an organic solvent to obtain a surface layer coating liquid. Next, the surface layer coating liquid is applied to the outer periphery of the base layer by a method such as ring coating, dip coating, or spray coating to form a coating film of the surface layer coating liquid. Next, if necessary, the coating film is dried at a temperature of, for example, 60 to 90°C to evaporate at least a part of the organic solvent in the coating film. Then, when the coating film contains the raw material of the binder resin, the coating film is cured by an appropriate method, and the surface layer can be formed by curing the coating film.
[0077] When forming the surface layer according to the second embodiment, it is preferable to irradiate the coating film with ultraviolet light while heating the belt at a temperature of 40 to 90° C. in the process of curing the binder resin, thereby curing the coating film to form the surface layer. As described above, by heating the coating film in the process of curing the coating film, the PFPE in the isolated domains in the coating film becomes easy to flow. In addition, as the polymerization of the raw materials (monomer, oligomer) of the binder resin in the coating film progresses, phase separation between the polymer and PFPE progresses, and the isolated domains are bonded to each other. Then, when the polymerization of the raw materials of the binder resin is finally completed to become the binder resin, the mutual connection structure of the domains containing PFPE is fixed, and the surface layer according to the second embodiment is formed. In addition, when obtaining a surface layer having an interconnected structure of domains containing PFPE, it is preferable to select a PFPE with low viscosity as the PFPE used. This is because isolated domains containing PFPE are easily bonded to each other during the curing process of the coating film. Therefore, in forming a surface layer having an interconnected structure of domains containing PFPE, it is preferable to adopt at least one selected from the group consisting of selecting a PFPE with low viscosity and heating the coating film during the curing of the coating film of the coating material for forming the surface layer.
[0078] [Outline and operation of electrophotographic image forming apparatus] FIG. 1 is a schematic cross-sectional view of an electrophotographic image forming apparatus (hereinafter, simply referred to as "image forming apparatus") showing the present embodiment. The image forming apparatus includes at least an image carrier that carries a toner image, and an intermediate transfer member that secondarily transfers the toner image, which has been primarily transferred from the image carrier, onto a recording material. The intermediate transfer member may be an electrophotographic member according to the present disclosure. The electrophotographic member may be an electrophotographic belt. For example, the electrophotographic member is an intermediate transfer belt. The electrophotographic belt or the intermediate transfer belt may have an endless shape. Hereinafter, an image forming apparatus using an intermediate transfer belt as an example of an electrophotographic member will be described.
[0079] As shown in FIG. 1, the image forming apparatus is provided with four process units as image forming means each including a charging means, an exposure means, a developing means, a cleaner, etc., around a photosensitive drum as an image carrier, and an image formed on the photosensitive drum in each process unit is transferred to an intermediate transfer belt 7 as an intermediate transfer member that moves adjacent to the photosensitive drum at a plurality of primary transfer portions. The toner images are transferred in sequence onto the intermediate transfer belt 7 to form a full-color toner image. After that, the toner images formed on the intermediate transfer belt 7 are transferred collectively onto a recording material (transfer material) such as paper in the secondary transfer section. The toner image on the recording material is then melted and fixed on the recording material by heat and pressure in the fixing section.
[0080] The image forming apparatus according to the present embodiment will be described in detail below. This image forming apparatus has four image forming units Y·M·C·K, numbered first through fourth, arranged in parallel from left to right in the drawing. Each image forming unit Y·M·C·K is an electrophotographic process mechanism of a laser scanning exposure type having the same configuration, and has a drum-type electrophotographic photoreceptor (hereinafter referred to as drum) 1 as an image carrier. Electrophotographic process means acting on this drum 1 include a charging roller 2 as charging means, an exposure device 3 as exposure means, a developing device 4 as developing means, a primary transfer roller 5 as primary transfer means, and a drum cleaner 6.
[0081] The intermediate transfer belt 7 is stretched between three parallel rollers: a drive and secondary transfer opposing roller 8, a tension and deviation correction roller 9, and a driven roller 10. The tension and deviation correction roller 9 is located on the first image forming unit Y side, the drive and secondary transfer opposing roller 8 is located on the fourth image forming unit K side, and the driven roller 10 is located below the drive and secondary transfer roller 8. The bottom surface of the intermediate transfer belt between the tension and deviation correction roller 9 and the driven roller 10 is in contact with the top surface of the drum 1 of each image forming unit Y, M, C, and K. The tension and deviation correction roller 9 can be adjusted in alignment to control the deviation of the intermediate transfer belt.
[0082] The primary transfer roller 5 of each image forming unit Y, M, C, K is disposed inside the intermediate transfer belt between the tension / shift correction roller 9 and the driven roller 10, and is pressed against the upper surface of the drum 1 with the intermediate transfer belt 7 sandwiched therebetween. The contact area between the drum 1 and the intermediate transfer belt 7 of each image forming unit Y, M, C, K is the primary transfer nip T1. The contact area between the intermediate transfer belt 7 and the secondary transfer roller 12 is the secondary transfer nip T2. A registration roller pair 13 is disposed upstream of the secondary transfer nip T2 in the recording material transport direction. In addition, a recording material transport belt device and a fixing device (not shown) are disposed in this order downstream of the secondary transfer nip T2 in the recording material transport direction.
[0083] The operation for forming a full-color image is as follows. The first to fourth image forming units Y, M, C, and K are driven at a predetermined control timing of the image formation sequence. This drive drives each drum 1 to rotate at the same predetermined speed in the clockwise direction of the arrow. The intermediate transfer belt 7 is also rotated at the same speed as the drum 1 in the counterclockwise direction of the arrow by the drive and secondary transfer opposing roller 8.
[0084] The surface of the rotating drum 1 is uniformly charged to a predetermined polarity and potential by a charging roller 2. The charged surface of the drum 1 is image-exposed by an exposure device 3. In this embodiment, the exposure device 3 is a laser scanner that outputs laser light modulated according to an image information signal to scan and expose the charged surface of the drum 1. As a result, an electrostatic image (electrostatic latent image) corresponding to the scanning and exposure pattern is formed on the drum surface. The formed electrostatic image is developed into a toner image by a developing device 4.
[0085] By the electrophotographic process as described above, the first image forming unit Y forms a yellow toner image corresponding to the yellow component image among the color separation component images of the full-color original image on the surface of the drum 1. The second image forming unit M forms a magenta toner image corresponding to the magenta component image, and the third image forming unit C forms a cyan toner image corresponding to the cyan component image, each at a predetermined control timing. The fourth image forming unit K forms a black component image. A corresponding black toner image is formed at a predetermined controlled timing.
[0086] Then, at the primary transfer nip T1 of the first image forming unit Y, the yellow toner image formed on the drum 1 is primarily transferred onto the intermediate transfer belt 7 which is being rotated. Next, at the primary transfer nip T1 of the second image forming unit M, the magenta toner image formed on the drum 1 is primarily transferred and superimposed on the yellow toner image on the intermediate transfer belt 7. Similarly, at the primary transfer nip T1 of the third image forming unit C and the fourth image forming unit K, the cyan toner image and the black toner image are sequentially primarily transferred onto the intermediate transfer belt 7.
[0087] That is, four color toner images, yellow, magenta, cyan, and black in total, are sequentially superimposed in a predetermined manner and superimposed (multiple) transferred onto the intermediate transfer belt 7, thereby forming a composite full-color unfixed toner image. In each primary transfer nip T1, the primary transfer of the toner image from the drum 1 to the intermediate transfer belt 7 is performed by applying a predetermined primary transfer bias to the primary transfer roller 5 from a primary transfer power supply unit (not shown), and electrostatically transferring the toner image from the drum 1 to the intermediate transfer belt 7.
[0088] The primary transfer bias is a DC voltage of a predetermined potential with a polarity opposite to the charge polarity of the toner. In each image forming unit Y, M, C, and K, the surface of the drum 1 after passing through the primary transfer nip is cleaned by the drum cleaner 6 to remove any residual toner from the primary transfer, and is then repeatedly used for image formation.
[0089] The unfixed toner image of the full-color image compositely formed on the intermediate transfer belt 7 as described above is conveyed by the continued rotation of the intermediate transfer belt 7 to reach the secondary transfer nip portion T2, which is the contact portion between the secondary transfer roller 12 and the intermediate transfer belt 7. Then, at the timing when the leading edge of the full-color unfixed toner image formed on the intermediate transfer belt 7 reaches the secondary transfer nip portion T2, the start of rotation of the registration roller pair 13 is controlled so that the print start position of the recording material P coincides with the secondary transfer nip portion T2. In the process in which the recording material P is nipped and conveyed through the secondary transfer nip portion T2, a secondary transfer bias of a predetermined potential and of a polarity opposite to the charge polarity of the toner is applied from the secondary transfer power supply portion to the secondary transfer roller 12. The secondary transfer bias is a DC voltage of a predetermined potential and of a polarity opposite to the charge polarity of the toner.
[0090] As a result, the full-color unfixed toner images on the intermediate transfer belt 7 are secondarily transferred all at once onto the recording material P. The recording material P that has left the secondary transfer nip portion T2 is separated from the intermediate transfer belt 7 and introduced into the fixing device by the recording material conveying belt device, where the toners of the respective color toner images are melted and mixed and fixed (fixed into a fixed image) on the surface of the recording material P as a full-color print image, and the full-color print is discharged outside the machine.
[0091] After the recording material is separated, the surface of the intermediate transfer belt 7 is cleaned by the intermediate transfer belt cleaner 11 to remove the secondary transfer residual toner during the subsequent rotation of the intermediate transfer belt 7, in preparation for the next image formation process. In the intermediate transfer belt cleaner 11, a cleaning blade is brought into contact with the surface of the belt 7 to scrape off the secondary transfer residual toner adhering to the belt surface, and the scraped off toner is collected in a collected toner box in the intermediate transfer belt cleaner 11 as collected toner.
[0092] A patch detection sensor 20 (toner image detection means) having a function of detecting image density is provided at a position facing the intermediate transfer belt portion stretched by the tension roller 10. This sensor optically detects reflected light and scattered light of light irradiated onto an adjustment toner image (patch image) formed on the intermediate transfer belt. During the period other than the period during which the toner image to be secondarily transferred to the recording material is primarily transferred, An adjustment toner image (patch image) is formed on the intermediate transfer belt. The image formation conditions are adjusted according to the result. In order to perform density measurement for controlling the image formation conditions more stably and accurately, it is preferable that the reflected light intensity from the surface of the intermediate transfer belt is equal to or higher than a certain level. This allows accurate density detection and makes it easier to suppress uneven density for each image. EXAMPLES
[0093] The present disclosure will be described in further detail below with reference to specific examples, but the present disclosure is not limited to the following examples.
[0094] First, the preparation of the copolymer, compound 1, will be described. <Preparation of Copolymer> (Copolymer 1) The materials shown in Table 1 below were mixed in a glass flask equipped with a stirrer, reflux condenser, nitrogen gas inlet tube, thermostatic bath, and thermometer at 20°C under a nitrogen atmosphere for 30 minutes, and then the reaction liquid was heated to a temperature of 85 to 90°C and reacted for 5 hours. The reaction was stopped by cooling with ice, and 1500 parts by mass of 2-propanol was added to obtain a precipitate. This precipitate was washed with a mixed solvent of n-butyl acetate:2-propanol = 1:5, and dried at a temperature of 80°C and a reduced pressure of 1325 Pa or less for 3 hours to obtain Copolymer 1.
[0095] [Table 1]
[0096] (Copolymer 2~12) Copolymers 2 to 12 were obtained in the same manner as for Copolymer 1, except that the materials and parts by mass used were changed as shown in Table 2. The materials used are as follows: Isobornyl acrylate (Tokyo Chemical Industry Co., Ltd.) 1H,1H,2H,2H-Nonafluorohexyl acrylate (Tokyo Chemical Industry Co., Ltd.) Methyl methacrylate (Tokyo Chemical Industry Co., Ltd.) 2,2,3,3,4,4,4-Heptafluorobutyl methacrylate (Tokyo Chemical Industry Co., Ltd.) Adamantan-1-yl acrylate (Tokyo Chemical Industry Co., Ltd.) Butyl methacrylate (Tokyo Chemical Industry Co., Ltd.)
[0097] <Measurement of weight average molecular weight> The weight-average molecular weight of the obtained copolymer was measured. The weight-average molecular weight was measured by dissolving the measurement sample in tetrahydrofuran (hereinafter also referred to as THF) to prepare a solution with a concentration of 0.2 mass%, and then using a gel permeation chromatograph (hereinafter also referred to as GPC) device GPC-104 (manufactured by Shodex). The molecular weight was measured using a column consisting of one each of "GPC KF-603" and "GPC KF-604" manufactured by Shodex, with the column temperature set at 40°C and the THF flow rate set at 1.0 mL / min. The weight-average molecular weight (Mw) of the sample was measured using a polystyrene standard substance with a known molecular weight (SM-105 manufactured by Shodex). ) was used to calculate the concentration from a calibration curve that had been prepared in advance.
[0098] Table 2 shows a list of the monomers used in the prepared copolymers and their amounts. Copolymers No. 11 and 12 are comparative copolymers that do not have the structure shown in formula (II). Table 3 shows the weight average molecular weights of the prepared copolymers measured by the above method. [Table 2]
[0099] [Table 3]
[0100] (PFPE) The PFPEs used in the examples and comparative examples are shown in Table 4. [Table 4]
[0101] [Example 1] The polyimide intermediate transfer belt itself installed in a Canon color multifunction printer (product name: iRC2620) was used as a base layer, and a surface layer was formed on this base layer by the method described below, to produce the electrophotographic belt of this example.
[0102] Dipentaerythritol hexaacrylate (DPEH) 7.0 parts by weight Pentaerythritol tetraacrylate (PETA) 15.0 parts by weight Pentaerythritol triacrylate (PETRA) 4.4 parts by weight Methyl ethyl ketone 26.4 parts by mass Celnax CX-Z210IP (Nissan Chemical Co., Ltd.) 4.5 parts by weight Photopolymerization initiator (BASF Irgacure (registered trademark) 184) 2.0 parts by mass PFPE2 14.8 parts by mass (Fluorolink® MD700, manufactured by Solvay Specialty Polymers) Copolymer 1 25.9 parts by mass These materials were mixed and dispersed using a stirring homogenizer (manufactured by AS ONE Co., Ltd.), and then dispersed using a dispersing device Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to prepare a paint for forming the surface layer. This paint was applied to the outer peripheral surface of the base layer and dried at a temperature of 70°C for 3 minutes to form a coating film of the paint. Next, the coating film was irradiated with 500 mJ / cm2 using a UV treatment device (manufactured by iGraphics Co., Ltd.) in an environment at a temperature of 25°C. 2 The coating was cured by irradiating ultraviolet rays of 1000 ohms to form a surface layer having a thickness of 4 μm. Thus, electrophotographic belt No. 1 was obtained. The electrophotographic belt No. 1 thus obtained was subjected to the following evaluations.
[0103] < Gloss measurement > When the domain of PFPE in the surface layer is large, specifically, when the average major axis exceeds 60 nm, the glossiness of the surface of the surface layer decreases. Therefore, as a guide to whether the domain of PFPE in the surface layer is small, the glossiness of the surface of the surface layer was measured by the following method. That is, the glossiness of the central portion in the width direction of the electrophotographic belt was measured at 20 points at equal intervals in the circumferential direction of the electrophotographic belt. A handy glossmeter (product name: PG-IIM; manufactured by Nippon Denshoku Industries Co., Ltd.) was used to measure the glossiness, the incident angle was set to 20°, and the arithmetic average value of the measured values at any 20 points was taken as the glossiness of the electrophotographic belt to be measured.
[0104] < Domain average major axis > The average major axis of the domain was observed by observing the cross section of the surface layer of the electrophotographic belt using a scanning electron microscope (S-4800 manufactured by Hitachi High-Technologies Corporation). First, a microtome (manufactured by Leica Microsystems, product name: EMUC7) was used to expose the cross section of the surface layer in the entire thickness direction. Then, the cross section of the surface layer in the thickness direction was divided into three equal parts. Then, 10 arbitrary points of each of the three parts were observed at a magnification of 20,000 times using the above-mentioned scanning electron microscope, and an SEM image was obtained in which at least one PFPE domain was confirmed in an area of 15 μm square. That is, 10 SEM images were prepared for each part (total 30 images). For each EM image, if there were 10 or fewer PFPE domains, the long diameter of all domains in the SEM image was measured. If there were more than 10 PFPE domains in the SEM image, 10 domains were arbitrarily selected and their long diameters were measured. The average long diameter of the PFPE domains obtained by performing the above observations and calculations on the 10 SEM images in each part was calculated.
[0105] <Image evaluation - Transferability evaluation> The electrophotographic belt of the Example or Comparative Example was attached to a color multifunction printer (product name: iRC2620; manufactured by Canon Inc.) in place of a polyimide intermediate transfer belt, and printing was performed. At this time, the images printed immediately after the start of printing and after 200,000 sheets were printed (after 200,000 repeated transfers) were evaluated. The image evaluation criteria are as follows: Rank A: No degradation in image quality due to defective secondary transfer is observed. Rank B: Degradation of image quality due to poor secondary transfer is observed. However, the area where degradation of image quality due to poor transfer occurs is 20% or less of the printed area. Rank C: The area where degradation of image quality due to poor secondary transfer occurs is more than 20% but not more than 50% of the printed area. Rank D: The area where degradation of image quality due to secondary transfer failure occurs is more than 50% of the printed area.
[0106] [Examples 2 to 10, Comparative Examples 1 to 4] Electrophotographic belts 102 to 110 according to Examples 2 to 10 and electrophotographic belts C101 to C102 according to Comparative Examples 1 and 2 were produced in the same manner as in Example 1, except that the copolymers shown in Table 5 were used instead of the copolymer 1 in Example 1. Then, the electrophotographic belts 102 to 110 and C101 to C102 were evaluated by the method described in Example 1. The evaluation results are shown in Table 6.
[0107] [Table 5]
[0108] [Table 6]
[0109] The electrophotographic belts of Examples 1 to 10 have a matrix-domain structure in the surface layer in the thickness direction, and the average major axis of the domain is 30 nm or more and 70 nm or less. The glossiness of the belt surface is high. Furthermore, the electrophotographic belts according to the examples hardly show a decrease in image quality due to transfer failure. Moreover, these properties are maintained for a long period of time.
[0110] In contrast, the electrophotographic belts according to Comparative Examples 1 and 2 have a matrix-domain structure in the thickness direction in the surface layer. In Comparative Examples 1 and 2, copolymers 11 and 12 are used, and these copolymers are dispersants that do not have the structure represented by formula (II). It is considered that the average major axis of the domains is therefore larger than that of Examples 1 to 10. It is also considered that the glossiness is reduced due to the large average major axis of the domains containing PFPE. Furthermore, it is considered that the size of the domains containing PFPE is larger than that of the Examples, and as a result, the PFPE that migrates to the surface of the surface layer is depleted at a relatively early stage, and as a result, the electrophotographic belts according to Comparative Examples 1 and 2 have a rank C in the evaluation result of the image after printing 200k sheets.
[0111] [Example 11] A polyimide intermediate transfer belt itself provided in a full-color multifunction printer (product name: imageRUNNER ADVANCE C5051; manufactured by Canon Inc.) was used as a base layer, and a surface layer was formed on this base layer by the method described below, to produce the electrophotographic belt 201 according to this embodiment.
[0112] Dipentaerythritol hexaacrylate 5.0 parts by mass Pentaerythritol tetraacrylate 8.0 parts by mass Pentaerythritol triacrylate 4.0 parts by mass 2-2-2 Trifluoroethanol 26.0 parts by mass Celnax CX-Z210IP (Nissan Chemical Co., Ltd.) 8.0 parts by weight Irgacure 184 (IGM Resin Co., Ltd.) 1.0 parts by weight PFPE1 (Solvay Specialty Polymers' Fomblin D2) 14.8 parts by mass Dispersant (obtained by volatilizing the solvent component of copolymer 1 and redissolving it in 2,2,2-trifluoroethanol to a solid content concentration of 20%) 14.8 parts by mass
[0113] These materials were mixed and dispersed with a stirring homogenizer (manufactured by AS ONE Corporation), and then dispersed with a dispersion device, a nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.), to obtain a mixed dispersion liquid. This was coated on the outer peripheral surface of the above-mentioned base layer, dried at 70 °C for 3 minutes, and then while heating the intermediate transfer body to 50 °C, it was cured with ultraviolet rays of 500 mJ / cm 2 to form a surface layer with a film thickness of 4 μm. Regarding the electrophotographic belt 201 thus obtained, the following evaluations were carried out.
[0114] <Removal of PFPE> A sample (length: 50 mm, width: 50 mm, thickness: the total thickness of the surface layer) cut out from the surface layer of the electrophotographic belt was immersed in 200 mL of a fluorine-based solvent containing 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (trade name: Asahiklin AE-3000; manufactured by AGC Inc.) in which PFPE is soluble, and ultrasonic waves were applied for 10 minutes using an ultrasonic cleaning device. Then, the sample was taken out from the fluorine-based solvent and left to dry in an environment at a temperature of 25 °C for 24 hours.
[0115] <Measurement of the domain void volume ratio after PFPE removal> After removing PFPE by the above procedure, the mass of a 50 mm long and 50 mm wide sample was measured. Then, the sample was immersed in PFPE oil with a known specific gravity (Fomblin M03, Fomblin Y04 (manufactured by Solvay Specialty Polymers)), and left under vacuum (100 Pa or less) for about 1 hour so that the PFPE oil would infiltrate into the voids. Then, the sample was taken out of the PFPE oil, the PFPE oil adhering to the surface was wiped off, and the mass was measured. From the mass difference before and after the PFPE oil infiltration, the volume of the infiltrated PFPE oil, that is, the volume of the voids was calculated, and the void volume ratio was calculated by dividing the volume of the voids by the volume of the surface layer of the intermediate transfer belt (50 mm long × 50 mm wide × thickness of the surface layer).
[0116] <Measurement of the area ratio and the number of openings of voids on the outer surface of the surface layer after PFPE removal> The surface corresponding to the outer surface of the surface layer of the sample after removing PFPE obtained by the above operation was observed with a scanning electron microscope, and an SEM image (magnification 10,000 times) of a rectangular observation region of 8 μm long and 11 μm wide was acquired. The resolution was set to 717 pixels in the vertical direction and 986 pixels in the horizontal direction so that the openings could be recognized. The acquired SEM image was converted into an 8-bit grayscale image using image processing software (product name: Image-J, manufactured by the National Institutes of Health (NIH), USA). After applying a median filter to the obtained grayscale image, further, binarization processing was performed using the above image processing software to obtain a binarized image. The YEN method was used for the binarization processing to discriminate between the portion corresponding to the openings in the SEM image and the portion corresponding to PFA. Then, the number of pixels of the portion corresponding to the openings in the obtained binarized image was counted. Also, the ratio of the number of pixels of the portion corresponding to the openings to the total number of pixels of the entire image was calculated. Here, the observation region was set at any 10 locations on the surface having openings in the surface layer, and the average value of the number of pixels of the portion corresponding to the openings counted from each observation region was taken as the number of openings, and by dividing by the area of the observation region, 1 μm 2The number of openings per observation area was calculated. The arithmetic mean value of the ratio calculated from each observation area was taken as the opening area ratio. Note that the observation areas were positioned so that they did not overlap each other.
[0117] <Image evaluation - Transferability evaluation> The produced electrophotographic belt was used in an electrophotographic image forming apparatus (product name: imageRUNNER The belt was attached as an intermediate transfer belt to a printer (Canon ADVANCE C5051). Using this electrophotographic image forming apparatus, electrophotographic images were printed. Here, image 1 printed immediately after printing began (initial stage), image 2 printed after 200,000 copies (after 200,000 repeated transfers (after 200k copies printed)), and image 3 printed after 600,000 copies (after 600,000 repeated transfers (after 600k copies printed)) were visually evaluated and rated according to the following criteria. Rank A: No degradation in image quality due to defective secondary transfer is observed. Rank B: Degradation of image quality due to poor secondary transfer is observed. However, the area where degradation of image quality due to poor transfer occurs is 20% or less of the printed area. Rank C: The area where degradation of image quality due to poor secondary transfer occurs is more than 20% but not more than 50% of the printed area. Rank D: The area where degradation of image quality due to secondary transfer failure occurs is more than 50% of the printed area.
[0118] [Examples 12 to 20, Comparative Examples 3 to 4] Electrophotographic belts 202 to 210 according to Examples 12 to 20 and electrophotographic belts C201 to C202 according to Comparative Examples 3 and 4 were produced in the same manner as in Example 11, except that the copolymers shown in Table 7 were used instead of the copolymer 1 in Example 11. The electrophotographic belts 202 to 210 and C201 to C202 were evaluated by the method described in Example 11. The evaluation results are shown in Table 8.
[0119] [Table 7]
[0120] [Table 8]
[0121] In the surface layers of electrophotographic belts C201 and C202 according to Comparative Examples 3 and 4, copolymers 11 and 12 are used, respectively, and these copolymers are dispersants that do not have the structure represented by formula (II). Therefore, it is considered that the function of dispersing PFPE is reduced, and the individual domain size is increased. As a result, the PFPE is exposed earlier, and it is considered that the secondary transfer efficiency is reduced when printing is repeated.
[0122] The present disclosure relates to the following configurations. (Configuration 1) 1. An electrophotographic member having at least a base layer and a surface layer, The surface layer of the electrophotographic member comprises the following components A, B, and C: A: Compound 1 having a structure represented by the following formula (I) and a structure represented by the following formula (II) B: Perfluoropolyether C: Binder resin TIFF2025018160000021.tif105168 In formula (I), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rf 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms, and in formula (II), R 21 represents a hydrogen atom or a methyl group, R 22 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rt 1 represents a structure having a polycyclic monoterpene. (Configuration 2) The electrophotographic member according to embodiment 1, wherein the polycyclic monoterpene-containing structure is represented by the following formula (Rt1-1): TIFF2025018160000022.tif31168 (configuration 3) Rf1 3. The electrophotographic member according to embodiment 1 or 2, wherein represents a perfluoroalkyl group having 3 or 4 carbon atoms. (Configuration 4) 4. The electrophotographic member according to any one of configurations 1 to 3, wherein the binder resin contains at least one resin selected from the group consisting of (meth)acrylic resins and epoxy resins. (Configuration 5) 5. The electrophotographic member according to any one of configurations 1 to 4, wherein the compound 1 has a weight average molecular weight of 15,000 to 80,000. (Configuration 6) When the perfluoropolyether is removed from the surface layer to produce a surface layer from which the perfluoropolyether has been removed, the surface layer from which the perfluoropolyether has been removed has voids having openings on its outer surface, 6. The electrophotographic member according to any one of configurations 1 to 5, wherein the ratio of the total volume of the voids to the volume of the surface layer from which the perfluoropolyether has been removed, assuming that the surface layer is solid, (void volume ratio) is 8.0 to 25.0%. (Configuration 7) The unit area (1 μm 2 ) of the outer surface of the surface layer from which the perfluoropolyether has been removed 2 7. The electrophotographic member according to claim 6, wherein the ratio of the total area of the openings per unit area is 10.0 to 35.0%. (Configuration 8) The unit area (1 μm 2 ) of the outer surface of the surface layer from which the perfluoropolyether has been removed 2 8. The electrophotographic member according to claim 6 or 7, wherein the number of the openings per one row is 10 to 500. (Configuration 9) 9. The electrophotographic member according to any one of configurations 1 to 8, wherein in the surface layer, the domain containing the perfluoropolyether and the binder resin are phase-separated. (Configuration 10) 10. The electrophotographic member according to any one of configurations 1 to 9, wherein the electrophotographic member is an electrophotographic belt having an endless shape. (Configuration 11) 1. An electrophotographic image forming apparatus, comprising: The electrophotographic image forming apparatus comprises: an image carrier that carries a toner image; an intermediate transfer member for secondarily transferring the toner image transferred from the image carrier to a recording material; 11. An electrophotographic image forming apparatus, wherein the intermediate transfer member is the electrophotographic member according to any one of Configurations 1 to 10. [Explanation of symbols]
[0123] 1 photosensitive drum, 2 charging roller, 3 exposure device, 4 developing device, 5 primary transfer roller, 6 drum cleaner, 7 intermediate transfer belt, 8 driving and secondary transfer opposing roller, 9 tension and deviation correction roller, 10 driven roller, 11 intermediate transfer body cleaner, 12 secondary transfer roller, 13 registration roller pair, 20 patch detection sensor, 31 base layer, 32 surface layer
Claims
1. 1. An electrophotographic member having at least a base layer and a surface layer, The electrophotographic member is characterized in that the surface layer contains the following A, B, and C: A: Compound 1 having a structure represented by the following formula (I) and a structure represented by the following formula (II) B: Perfluoropolyether C: Binder resin In formula (I), R 11 represents a hydrogen atom or a methyl group, R 12 represents a single bond or an alkylene group having 1 to 3 carbon atoms; Rf 1 represents a perfluoroalkyl group having 1 to 4 carbon atoms, and in formula (II), R 21 represents a hydrogen atom or a methyl group, R 22 represents a single bond or an alkylene group having 1 to 3 carbon atoms; 1 represents a structure having a polycyclic monoterpene.
2. 2. The electrophotographic member according to claim 1, wherein the polycyclic monoterpene-containing structure is represented by the following formula (Rt1-1):
3. The Rf 1 2. The electrophotographic member of claim 1, wherein R is a perfluoroalkyl group having 3 or 4 carbon atoms.
4. 2. The electrophotographic member according to claim 1, wherein the binder resin comprises at least one resin selected from the group consisting of (meth)acrylic resins and epoxy resins.
5. 2. The electrophotographic member according to claim 1, wherein the weight average molecular weight of said compound 1 is from 15,000 to 80,000.
6. When the perfluoropolyether is removed from the surface layer to produce a surface layer from which the perfluoropolyether has been removed, the surface layer from which the perfluoropolyether has been removed has voids having openings on its outer surface, 2. The electrophotographic member according to claim 1, wherein the ratio of the total volume of the voids to the volume of the surface layer from which the perfluoropolyether has been removed, assuming that the surface layer is solid, is 8.0 to 25.0% (void volume ratio).
7. The unit area (1 μm 2 ) of the outer surface of the surface layer from which the perfluoropolyether has been removed 2 7. The electrophotographic member of claim 6, wherein the percentage of the total area of said openings per unit area is from 10.0 to 35.0%.
8. The unit area (1 μm 2 ) of the outer surface of the surface layer from which the perfluoropolyether has been removed 2 8. The electrophotographic member of claim 7 wherein the number of said openings per layer is from 10 to 500.
9. 2. The electrophotographic member according to claim 1, wherein in said surface layer, said domain containing said perfluoropolyether and said binder resin are phase-separated.
10. 2. The electrophotographic member of claim 1 wherein said electrophotographic member is an electrophotographic belt having an endless configuration.
11. 1. An electrophotographic image forming apparatus, comprising: The electrophotographic image forming apparatus comprises: an image carrier that carries a toner image; an intermediate transfer member for secondarily transferring the toner image transferred from the image carrier onto a recording material; 11. An electrophotographic image forming apparatus, wherein the intermediate transfer member is the electrophotographic member according to claim 1.
Citation Information
Patent Citations
Intermediate transfer body for electrophotography, and electrophotographic device
JP2013231964A
Electrophotographic belt and electrophotographic image formation device
JP2022167788A